A new Tier 3 method to calculate methane emission inventory for ruminants. (1st February 2019) - Eugène, M.; Sauvant, D.; Nozière, P.; Viallard, D.; Oueslati, K.; Lherm, M.; Mathias, E.; Doreau, M.
Abstract: Livestock is the main source of methane (CH4 ) emissions. It is important to accurately determine emissions from ruminants that meet standardized international guidelines for national greenhouse gas inventories. A new method to improve the accuracy of CH4 emissions that complies with IPCC rules for a Tier 3 method is described and evaluated. This method, developed by INRA (French Institute for Agricultural Research), was applied to the French inventory of CH4 emissions by ruminants and compared with the IPCC Tier 2 method. For enteric CH4, depending on the animal category, the INRA CH4 emission estimates lay between 88% and 114% of IPCC's. The INRA/IPCC ratio for enteric emission was close to unity and did not differ between methods ( P = 0.43) for adult cows (i.e. most cattle). In France, feedlot manure is stored in aerobic conditions, and so the INRA/IPCC fit for manure emission was poorer (P < 0.05). The INRA/IPCC fit for enteric CH4 was very close between methods to that for total CH4 ( P = 0.39), enteric CH4 representing 93% of total emissions. The main improvement is the use of a robust equation (from numerous data and diets), based on digestible organic matter intake (DOMI) corrected for the digestive interactions, to predict CH4 consistently from enteric and manure sources. It was developed for the French livestock inventory but is customizable for other countries. This new improved CH4 estimation method, based on equations from a large literature database, complies with IPCC rules for a Tier 3 method. Highlights: A new method improves the estimation of methane emissions for GHG inventory. Estimations of enteric and manure CH4 are consistent. Robust CH4 predictions are based on INRA's revised ruminant feeding system. This method can be adapted to many countries.